2014
DOI: 10.2298/vsp1402156s
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of endobronchial tuberculosis

Abstract: EBTB was more frequent among men, and among people in their fifties in our country. Detailed bronchoscopic examination, correlated with clinical and laboratory findings, will improve diagnostic rate and provide timely therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…In our study, bronchoscopy showed that TBTB mainly involves the upper lobes, consistent with previous reports [8,28,29]. This finding is likely because PTB commonly affects the upper lobes and obstructed drainage of secretions usually occurs in the upper lobe bronchus.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, bronchoscopy showed that TBTB mainly involves the upper lobes, consistent with previous reports [8,28,29]. This finding is likely because PTB commonly affects the upper lobes and obstructed drainage of secretions usually occurs in the upper lobe bronchus.…”
Section: Discussionsupporting
confidence: 92%
“…Cough is the most common symptom and present in 70-80% of the patient (12,21,22). Cough could be dry or with bronchorrea especially when EBTB is a part of cavitory TB (23).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Cough could be dry or with bronchorrea especially when EBTB is a part of cavitory TB (23). Fever is usually low grade but may become marked with advanced cavitory disease (12,22). Hemoptysis may occur in 15-40% of the patient but is usually mild but sometime massive hemoptysis may occur (22).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical features of the EBTB are nonspecific and they differ between various types and stages of endobronchial tuberculosis [ 8 ]. Common symptoms are cough, hemoptysis, sputum production, wheezing, chest pain, fever, and dyspnea [ 8 , 9 ]. Bronchial hyperreactivity can be seen in a considerable number of patients with EBTB.…”
Section: Discussionmentioning
confidence: 99%